2021
DOI: 10.1136/heartjnl-2020-318907
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of left atrial dilation in aortic regurgitation due to bicuspid aortic valve

Abstract: ObjectiveTo investigate the prognostic value of left atrial volume index (LAVI) in patients with moderate to severe aortic regurgitation (AR) and bicuspid aortic valve (BAV).Methods554 individuals (45 (IQR 33–57) years, 80% male) with BAV and moderate or severe AR were selected from an international, multicentre registry. The association between LAVI and the combined endpoint of all-cause mortality or aortic valve surgery was investigated with Cox proportional hazard regression analyses.ResultsDilated LAVI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A recent large registry study showed the prognostic importance of LA dilatation in patients with BAV and moderate or severe aortic regurgitation. 26 In our study, LA enlargement also showed a significant prognostic association with arrhythmia-free survival, as did E/e’ ratio and LV mass index. GLS and LVEF were not associated with arrhythmia-free survival.…”
Section: Discussionsupporting
confidence: 65%
“…A recent large registry study showed the prognostic importance of LA dilatation in patients with BAV and moderate or severe aortic regurgitation. 26 In our study, LA enlargement also showed a significant prognostic association with arrhythmia-free survival, as did E/e’ ratio and LV mass index. GLS and LVEF were not associated with arrhythmia-free survival.…”
Section: Discussionsupporting
confidence: 65%
“…A direct correlation between LA reservoir function and PH has been reported in patients with moderate or severe AR, with a 6% increase of PH risk for each unit of LA strain decrease ( 151 ). Recently, a large study on 554 patients with bicuspid aortic valve and moderate or severe AR showed that the LA enlargement (LAVI ≥ 35 ml/m 2 ) was independently associated with adverse outcome (aortic valve surgery or mortality), when compared with patients with normal LAVi (43 and 60% vs. 23 and 36%, at 1 and 5 years of follow-up, respectively, p < 0.001) ( 161 ). In addition to LA enlargement, its contractile function is impaired in severe AR, as reported in 65 patients scheduled for AVR and assessed with 2DSTE.…”
Section: La Mechanics In Hf Stagesmentioning
confidence: 99%
“…Additionally, aortic regurgitation (AR) was identified as a predictor of AS regardless of valve morphology, and varying degrees of AR was detected in one in four patients with BAV. Other studies have also reported the incidence of AR in patients with BAV to range from 13 to 65% [34,35]. Statistically, the median ejection fraction (EF) was within the normal range.…”
Section: Features Importancementioning
confidence: 89%